P2P computing for large tree exploration-based exact optimisation. (6th August 2009) - Mehdi, M.; Mezmaz, M.; Melab, N.; Talbi, E-G.; , P. Bouvry
The Branch and Bound (B&B) algorithm is one of the most used methods to solve in an exact way combinatorial optimisation problems. In a previous article, we proposed a new approach of the parallel B&B algorithm for distributed systems using the farmer-worker paradigm. However, the new farmer-worker approach has a disadvantage: some nodes of the B&B tree can be explored by several B&B processes. To prevent this redundant work and speed up, we propose a new P2P approach inspired from the strategies of existing P2P systems like Napster and JXTA. Validation is performed by experimenting the two approaches on mono-objective flow-shop problem benchmarks using 500 processors belonging to the French national grid, Grid'5000. The obtained results prove the efficiency of the proposed P2P approach. Indeed, the execution time obtained with the P2P version, even if more communicative, is better than the farmer-worker's one.